Trends in prevalence of selected opportunistic infections associated with HIV/AIDS in Uganda - Rubaihayo, John; Tumwesigye, Nazarius M; Konde-Lule, Joseph (BMC Infectious Diseases, 2015)
After more than a decade of establishing and expanding access to highly active antiretroviral therapy (HAART), empirical evidence on its impact on trends of opportunistic infections (OIs) associated with the deadly human immunodeficiency virus (HIV) in resource poor settings is scarce. The primary objective of this study was to assess the effect of HAART coverage on trends of five most common OIs in Uganda.
Keywords: Human Immunodeficiency Virus; Cryptococcal Meningitis; Herpes Zoster